South–South Migration and Security Risks: Political Islam and Violent Extremism in the Shadow of Globalisation in Bangladesh. (September 2017) - Hasan, Mubashar
Against the backdrop of 2016 terrorist attack in Dhaka, this article argues that in the terrain of Bangladeshi literatures on migration, little is explored about the impact of south–south migration in unleashing security threat to Bangladesh. This article offers a historic trajectory of south–south migration and security threat to Bangladeshi state. It argues that while it is important to understand migration from various point of views, scholars have ignored to explore the nexus between migration and security threat of the sender state. This article explains why to some Muslim migrants of Bangladesh, bad ideas such as terrorism may seem to form an option and how globalisation played a role in fostering bad ideas. It proposes that scholars of migration require to indulge in further research to understand the nexus between outward migration and security threat to Bangladesh.